2019
DOI: 10.1177/0011128719834564
|View full text |Cite
|
Sign up to set email alerts
|

Co-offending Group Composition and Violence: The Impact of Sex, Age, and Group Size on Co-offending Violence

Abstract: Co-offenders commit more violent offenses than solo offenders, in part due to collective behavior processes that exacerbate behavior in groups. But, different co-offenders likely experience these processes differently. Following this, this research examines the relationship between co-offending, group sex and age composition, and violence using National Incident–Based Reporting System (NIBRS) data. Results indicate that male groups are more likely to seriously injure victims, but that sex composition matters m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 66 publications
1
24
0
2
Order By: Relevance
“…The current study addressed this gap, and showed via its longitudinal design that co-offending is an accelerating force that links the development of best friends' delinquency with the development of adolescents' delinquency. Although cooffending has been known to exacerbate delinquency in real-time as groups are more violent than individuals (Lantz 2020), the current study additionally shows that cooffending has the potential to exacerbate the codevelopment between friends' delinquency and adolescents' delinquency in the long-term too. Particularly among adolescents who co-offend with friends, the development of their friends' delinquency is more strongly related to the development of their own delinquency.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The current study addressed this gap, and showed via its longitudinal design that co-offending is an accelerating force that links the development of best friends' delinquency with the development of adolescents' delinquency. Although cooffending has been known to exacerbate delinquency in real-time as groups are more violent than individuals (Lantz 2020), the current study additionally shows that cooffending has the potential to exacerbate the codevelopment between friends' delinquency and adolescents' delinquency in the long-term too. Particularly among adolescents who co-offend with friends, the development of their friends' delinquency is more strongly related to the development of their own delinquency.…”
Section: Discussionmentioning
confidence: 53%
“…Answer categories ranged from "fully untrue" (=1) to "fully true" (=4). This sub-scale has been validated in previous studies (Van Gelder et al 2018, 2020. Mean scores were computed from the items on the scale.…”
Section: Impulsivitymentioning
confidence: 99%
“…The data also include detailed information on co-offending and demographic information for each recorded co-offender. Finally, these data also include a substantial number of cases, allowing for the examination of statistically rare, but theoretically significant groups, like robberies committed by all-female groups (Lantz, 2019). Taken together, these advantages situate NIBRS as an extremely useful data source for the examination of the group hazard.…”
Section: Methodsmentioning
confidence: 99%
“…Relatedly, past work has shown the importance of understanding aspects of co-offending networks—such as the group size, strength of ties, and breakdown of gender and age—for understanding how co-offending impacts outcomes (e.g., Andersen, 2019; Lantz, 2020b: Lantz & Hutchison, 2015; Ouellet et al, 2013). For example, Andersen (2019) confirmed that recidivism was more likely for those had more direct co-offending ties (i.e., connections with more unique co-offenders), even though the study did not observe repeated co-offenses with the co-offenders acquired before incarceration.…”
Section: Discussionmentioning
confidence: 99%